Efektifitas Penerapan Outbound Training Dalam Meningkatkan Kemampuan Resolusi Konflik Interpersonal Pada Remaja - Ramadhani, Hetti Sari; Rahmasari, Diana (Universitas Negeri Surabaya, 2011)
This study aims to test the effectiveness of outbound training in improving interpersonal conflict resolution skills in adolescents. Subjects were adolescents outbound training participants with age ranges between 16-19 years old on the Team Survival Outbound Prigen Pasuruan. The design of this study was a true experiment, with 10 participants who were registered as outbound training participant was being assigned as experiment group and 10 participants who were not registered as outbound training participant was being assigned to control group Sampling technique used in this research was purposive sampling by selecting participants with low conflict resolution score. Data collecting method used was interpersonal conflict resolution questionnaire which resulting in an ordinal scale and was analysed using parametric statistic with t-test paired sample and independent t-test. Obtained score was t = 9.635 and p=0.000 (p<0.025), which means that the research hypothesis was accepted. In other words, there were a significant difference between adolescence interpersonal conflict resolution score prior- and post-intervention (outbound training) in Î± = 0.05%. Obtained score was t = 5.069 and p=0.000 (p<0.025), which means that the research hypothesis was accepted. It can be concluded, that there were a significant difference between adolescence interpersonal conflict resolution score prior- and post-intervention (outbound training) in Î± = 0.05%. Based on those results, it can be concluded that an effective implementation of outbound training can increase interpersonal conflict resolution skill in adolescence.Abstrak: Penelitian ini bertujuan untuk menguji keefektifan outbound training dalam meningkatkan kemampuan resolusi konflik interpersonal pada remaja. Subjek penelitian adalah peserta remaja outbound training dengan rentang usia 16-19 tahun The Survival Outbound Team Prigen Pasuruan. Penelitian ini menggunakan true experiment yaitu kelompok eksperimen adalah 10 remaja yang terdaftar sebagai peserta outbound training dan kelompok kontrol adalah 10 remaja yang tidak terdaftar sebagai peserta outbound training. Pengambilan subjek penelitian menggunakan teknik purposive sampling yakni mereka yang memiliki skor resolusi konflik interpersonal rendah. Pengumpulan data menggunakan angket resolusi konflik interpersonal yang dinyatakan dalam bentuk ordinal dan menggunakan statistikÂ parametrik dengan paired sampel t test dan independent t test. Hasil analisis data diperoleh nilai t sebesar 9,635 dan p=0,000 (p<0,025) sehingga hipotesis penelitian diterima. Artinya, ada perbedaan yang signifikan terhadap skor resolusi konflik interpersonal remaja antara sebelum dan sesudah diberikan outbound training pada taraf Î± = 0,05%. Diperoleh nilai t sebesar 5,069 dan p=0,000 (p<0,025) sehingga hipotesis penelitian diterima. Artinya, ada perbedaan yang signifikan terhadap skor resolusi konflik interpersonal antara remaja yang mendapat outbound training dan remaja yang tidak mendapat outbound training pada taraf Î± = 0,05%. Dari data analisis, dapat disimpulkan bahwa penerapan outbound training efektif dalam meningkatkan kemampuan resolusi konflik interpersonal remaja.